Wine production on Istria family farms - Anita Silvana ILAK PERŠURIĆ; Ana TEŽAK (Acta Agriculturae Slovenica)
Viticulture in Istria is considered as a pillar in the agricultural economy. Wine tourism is present in Istria in the last two decades along with the establishment of wine roads. There are three existing wine roads in Istria. One of the activities on the wine road is wine tasting. From the perspective of the family farms it is a service that offers the farm product (wine) directly to consumers. We questioned farmers on Istrian wine roads and partners in Vinistra (the Istrian association of grape and wine producers) the wine offer and concluded that most wine cellars offer wines like Malvazija istarska and Teran from autochthonous varieties, Chardonnay and Cabernet Sauvignon from introduced grape varieties, was examined. Very few wine cellars offered wines like Borgognja, Hrvatica or other. Also issues like consumer’s preferences and possible solutions of enhancing the wine offer and wine roads of Istria in general were referred.